Human trafficking: emerging legal issues and applications - Cronin, Nora M.; Ellis, Kimberly A.; Blair, Peter W. Jr (Lawyers & Judges Publishing Company, Inc., 2017)
Labor trafficking : the Garcia case and beyond / by Gonzalo Martinez de Vedia -- Human trafficking in the drug trade : lessons for attorneys from the Mary Jane Veloso case / by Felicity Gerry, QC -- The New York approach : a lawyer's guide to human trafficking intervention courts / by Nicole Campion -- Human trafficking and exploitation in Australia / by Fiona McLeod, SC -- Using digital technologies to combat human trafficking : privacy implications / by Felicity Gerry QC, Julia Muraszkiewicz, and Niovi Vavoula --Human trafficking in the dark : sex trafficking on the dark web / by Bryanne Perlanski -- Using the new social influence model (SIM) to pursue justice for trafficking victims / by Nora M. Cronin and Alan W. Scheflin -- Trauma in sex-trafficked children / by Melissa L. Breger -- The human rights argument in human trafficking : duty to identify victims / by Julia Muraszkiewicz -- Gender issues in human trafficking : empowering women and girls through awareness and law / by Felicity Gerry QC and Catarina Sjãqlin -- Human trafficking and cults / by Robin Boyle Laisure